Defining the substrate specificity of an unusual acyltransferase: a step towards the production of an advanced biofuel - Bansal, Sunil (Kansas State University, 2016)
The direct use of vegetable oils as a biofuel suffers from problems such as high viscosity, low volatility and poor cold temperature properties. 3-acetyl-1,2-diacyl-sn-glycerols (acetyl-TAGs) have lower viscosity and freezing temperature than regular vegetable oils. However, by modifying their fatty acid composition, further improvement in their fuel properties is possible. Our goal was to develop plants that synthesize seed oils with further improved fuel properties. Euonymus alatus diacylglycerol acetyltransferase (EaDAcT) synthesizes acetyl-TAGs by the acetyl-CoA dependent acylation of diacylglycerol (DAG). Knowledge of the substrate specificity of EaDAcT for its acetyl-CoA donor and DAG acceptor substrates is important to generate the required acetyl-TAG composition in seed oil. A rapid method to quantify acetyl-TAGs was developed based on electrospray ionization mass spectrometry to gain information about the substrate specificity of EaDAcT. This method is as accurate and more rapid than the traditional radiolabeled substrate based assay and additionally provides information on acetyl-TAG molecular species present. Using this assay, EaDAcT specificity for different chain length acyl-CoA and DAGs was tested. It was found that although EaDAcT can use other short chain length acyl-CoAs as acyl donors, it has high preference for acetyl-CoA. Further, EaDAcT can acetylate a variety of DAGs with short, medium and long chain length fatty acids with high preference for DAGs containing unsaturated fatty acids. To generate acetyl-TAGs with lower molecular mass, EaDAcT was transformed into transgenic Camelina sativa lines producing high amounts of medium chain fatty acids (MCFAs). EaDAcT expression was also combined with the knockdown of DGAT1 and PDAT enzymes, which compete with EaDAcT for their common DAG substrate. High acetyl-TAG yielding homozygous T3 transgenic lines were generated but the incorporation of MCFAs into acetyl-TAGs was inefficient. A small increase in the viscosity of acetyl-TAGs from these lines was observed compared to acetyl-TAGs produced in wild type Camelina plant. The combined effect of insufficient lowering of molecular mass and increased fatty acid saturation levels of acetyl-TAGs might be responsible for this increased viscosity. Overall, it was concluded that the molecular mass and the saturation levels of fatty acids of acetyl-TAGs need to be considered at the same time in future attempts to further decrease their viscosity.
Keywords: Acetyl-TAGs; Substrate specificity; Metabolic engineering; Low viscosity biofuel; Acyltransferase; Camelina; Alternative Energy (0363); Biochemistry (0487); Plant Sciences (0479)